Evaluation of the total sulfur amino acid requirement of finishing pigs - J A Loughmiller; J W Smith II; J R Bergstrom; Robert D Goodband; Michael D Tokach; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1996)
Sixty four gilts (initially 120 lb) were used to evaluate the effects of increasing total sulfur amino acid (TSAA):lysine ratios on growth performance and carcass characteristics. Diets included two levels of lysine (.55% and .70% total lysine) and three TSAA:lysine ratios (60, 65, and 70% of lysine) arranged in a 2 x 3 factorial. A tendency for a lysine x TSAA interaction was observed for ADG and ADFI. Increasing TSAA:lysine ratio decreased ADG and ADFI in pigs fed .55% lysine; however, ADG and ADFI were increased in pigs fed .70% lysine and 65% TSAA:lysine. Pigs fed .70% lysine had improved ADG, F/G and 10th rib fat depth compared to those fed .55% lysine. However, no effects were observed with increasing TSAA: lysine ratios. These results suggest that the TSAA requirement of finishing pigs is not greater than 60% of total lysine.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Finishing pigs; Methionine; Amino acids